Applying the Concept of Civil State for Public Management - Sivarat, Napatorn; Yupas, Assoc. Prof. Dr. Yupaporn; Kenaphoom, Assoc. Prof. Dr. Sanya (Journal for Developing the Social and Community, 2017)
Effort for using the Civil State Concept as the public management among condition that the country still lacks mechanism of good governance, therefore, the way to recover situation for economy and society stability need to rely on power of people all of country. The civil state concept will be the good way to develop country to thrive steadily. These concept is to bring together the five sectors namely; (1) Government sector: which is considered to be large organization of personnel spread throughout the area with knowledge, budget and role based on responsibility. (2) Private sector is well-managed and has streamlined capital. (3) People sector can produce goods and service with loving of homeland. (4) Scholar sector has knowledge and technology by research continuously. And (5) Civil society, depth work, follow always and has many networks.